EVALUASI PROGRAM KLAMPID NEW GENERATION UNTUK PEMUTAKHIRAN BIODATA DIGITAL DALAM MENINGKATKAN LAYANAN PUBLIK DI KELURAHAN PENJARINGANSARI - Ningrum, Dhea Pramestya; Pertiwi, Vidya Imanuari (Jurnal PubBis, 2025)
The Pejaringansari Village is still facing challenges in achieving the target of updating population administration data, particularly the updating of family card data, which remains significantly delayed. As an effort to address this issue, Pejaringansari Village optimizes its biodata updating services through the implementation of Klampid New Generation. The purpose of this study is to analyze and obtain a specific description of the success of the Klampid New Generation Program for Digital Biodata Updates in Improving Public Services in Pejaringansari Village. This study uses a qualitative descriptive method with an approach focused on qualitative analysis. Data sources were selected using purposive sampling techniques, and data collection was conducted through observation, interviews with five informants, and documentation. The results show that the Klampid New Generation Program for Digital Biodata Updates in Improving Public Services in Pejaringansari Village has been successfully implemented. This is evident through five assessment indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy, all of which demonstrate more efficient, effective, fair, responsive, and accurate public services. The implications of this study indicate that the biodata updating service through KNG has made a significant contribution to improving the quality of public services and digital biodata updates. Therefore, there is a need for sustained commitment from the local government to expand the implementation and strengthen this system to support the development of a more effective and efficient government. Keywords : Program Evaluation, KNG, Biodata Update